Pengembangan Sistem Informasi Persediaan Obat Berbasis Android pada Puskesmas Lakologou - Jabal Nur; Wa Ode Rahma Agus Udaya Manarfa; Andi Nasri; Lintang Lintang (JURNAL INFORMATIKA, 2025)
The adoption of digital technology has become a strategic necessity across various sectors, including healthcare services. Lakologou Public Health Center still performs manual procedures for recording and reporting drug inventory, which leads to inefficiencies, delayed information, and data inaccuracies. This study aims to develop an Android-based drug inventory information system that supports more effective and accurate management of stock, distribution, and reporting. A descriptive research method was employed through observations, interviews with the Head of the Health Center and pharmacy staff, as well as literature studies from relevant sources. System functionality was evaluated using Black Box Testing to ensure that all features operated according to user requirements. The findings indicate that the proposed system facilitates recording of incoming and outgoing drugs, monitoring stock availability, and generating daily, weekly, monthly, and annual reports automatically. The system involves three main actors: (1) Admins, who manage employee data, clinic services, and patient registration, as well as access reports; (2) Pharmacy Officers, who manage stock and drug transactions; and (3) Doctors, who monitor drug availability and provide prescriptions. Overall, the implementation of this Android-based system improves operational efficiency and information accuracy in drug inventory management at Lakologou Public Health Center.